Use of paediatric donor tissue in Descemet stripping endothelial keratoplasty. Issue 12 (23rd July 2009) - Huang, T; Wang, Y; Hu, A; Luo, Y; Chen, J
Abstract : Aims: To evaluate the feasibility, efficacy and postoperative complications of Descemet stripping endothelial keratoplasty (DSEK) with paediatric donor tissue. Methods: Retrospective non-comparative interventional case series. Seven consecutive cases (seven eyes) of pseudophakic bullous keratopathy were treated with DSEK using paediatric donor tissue and followed up for 12 to 18 months. Data collected included best spectacle-corrected visual acuity, spherical equivalent refractive error, corneal astigmatism, corneal curvature and endothelial cell density. Results: DSEK was successfully performed in six out of seven eyes with paediatric donor graft; one paediatric donor graft perforated during dissection. All paediatric tissue was unfolded using the "hitch suture" technique and supported with plenty of air. No graft dislocation occurred. At 12 months postoperatively, the cornea was clear in all eyes; the best spectacle-corrected visual acuity ranged from 20/67 to 20/32; the average spherical equivalent refractive error was 1.9 (0.5) dioptres; the average corneal astigmatism was 2.2 (0.6) dioptres; the average corneal curvature was 45.2 (1.6) dioptres; and the average endothelial cell density was 2247.7 (74.3) cells/mm 2 (41.4 (3.7)% of endothelial cell loss). Conclusion: With high postoperative endothelial cell counts, low graft dislocation rate and absence of high myopic shifts, paediatric donor tissue can be successfully used in DSEK.